TEORI BELAJAR DAN IMPLIKASINYA TERHADAP PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM (PAI) - Family, Ade Vera Yantika; Agus Pahrudin; Agus Jatmiko; Koderi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The relationship between learning theories and their consequences for the creation of the Islamic Religious Education (PAI) curriculum is examined in this paper. The requirement of integrating cognitive, behavioral, and constructivist learning theories, the challenges of successful implementation, and the need to match the curriculum with contemporary educational practices are some of the main topics covered. The goal of the study is to examine how different learning theories might improve the PAI curriculum and give students a more interesting and fulfilling learning environment. Using a qualitative methodology, the study collected information on current practices and difficulties by conducting interviews with curriculum developers and instructors as well as literature reviews. The results show that incorporating different learning theories into the curriculum enhances it and fosters students' moral and critical thinking. In order for teachers to successfully implement these theoretical frameworks in their instruction, the study also highlights the significance of continual professional development. In order to fulfill the varied requirements of kids, curricular policymakers should embrace a dynamic and inclusive approach to PAI, according to the research's conclusions. Keywords: Learning theories, Islamic Religious Education, curriculum development, educational practices, qualitative research, teacher development.